Pendidikan Anti Korupsi di SMA Kabupaten Pacitan - Mukodi Mukodi (LPPM Press, 2013)
Rampant corruption occurred recently is essentially a portrait of the accumulated actions of society in carrying out the activities of daily life. Itmust be recognized that educational institutions , especially the world of schooling also donates seeds of the corruptive behaviour, manipulative andnepotism in a certain level, primarily in the transfer of knowledge and the transfer of value to the learning process in the classroom cubicles, and schools.The process of awareness against the corruption must be inculcated and struggled for its existence in order that Indonesia will be free from the bondage ofthe corruption crime soon. Anti- corruption education in high school Pacitan is an alternative solution- to unravel the